Beclin 1 promotes endosome recruitment of hepatocyte growth factor tyrosine kinase substrate (HRS) to suppress tumor proliferation - Matthew-Onabanjo, Asia N. (Cancer Res, 2019)
Beclin 1 has non-autophagic functions that include its ability to regulate endocytic receptor trafficking. However, the contribution of this function to tumor suppression is poorly understood. Here, we provide in vivo evidence that Beclin 1 suppresses tumor proliferation by regulating the endocytic trafficking and degradation of the epidermal growth factor (EGFR) and transferrin (TFR1) receptors. Beclin 1 promoted endosomal recruitment of hepatocyte growth factor tyrosine kinase substrate (HRS), which was necessary for sorting surface receptors to intraluminal vesicles for signal silencing and lysosomal degradation. In tumors with low Beclin 1 expression, endosomal HRS recruitment was diminished and receptor function was sustained. Collectively, our results demonstrate a novel role for Beclin 1 in impeding tumor growth by coordinating the regulation of key growth factor and nutrient receptors. These data provide an explanation for how low levels of Beclin 1 facilitate tumor proliferation and contribute to poor cancer outcomes.